مساهمة المقاولة من الباطن في تحسين القدرة التنافسية للمؤسسة الاقتصادية دراسة حالة مركب تمييع الغاز الطبيعي بسكيكدة - غلاب, نعيمة; زغيب, مليكة; شايب, حنان (Sciences humaines; Vol. 25 (2012): SCIENCES HUMAINES, 2014)
أدت التطورات المتلاحقة التي شهدها العالم في العقود الأخيرة، إلى احتدام المنافسة بين منظمات الأعمال و جعلت بقاءها و استمرارها مرهون بمدى قدرتها على مجابهة غيرها من المنافسين المحليين منهم و الدوليين.هذه الأوضاع دفعت المؤسسات الاقتصادية إلى تبني إستراتيجيات تمكنها من التركيز على قلب النشاط و تحقيق الاستغلال الأمثل لامتيازاتها التنافسية ، مما يعزز من قدرتها على الصمود في وجه المنافسة الشرسة، و قد هذا باستعمال إستراتيجيات المنح الخارجي و في مقدمتها المقاولة من الباطن.     توصلت دراستنا إلى وجود اختلال في تطبيق هذه الإستراتيجية نتج عنه مشاكل عديدة،بالرغم من بعض التحسن في القدرة التنافسية.     Abstract:   Consecutive developments seen in the world in recent decades has leaded to increased competition between organizations, and made their existence and continuity associated with the extent of their ability to confront other local competitors as well international. These situations have pushed companies to adopt strategies to focus on core business and make the best use of their competitive advantages, enhancing their competitiveness, using the strategies of outsourcing, the most important is subcontracting. Our study focused on the reality of this strategy and its impact on competitiveness in Complex natural gas liquefaction in Skikda. The study leads to an imbalance in the implementation of the strategy which led to many problems, despite some improvement in competitiveness.